IDENTIFICATION AND RESEARCH OF ANTIBACTERIAL POTENTIAL OF ACTINOMYCETES STRAINS ISOLATED FROM THE RHIZOSPHERE OF OLIVE TREES IN THE REGION OF SOUK AHRAS. - ATBI Oumaima; SELAIMIA Likaa Rawen (My University, 2025)
This study aimed to investigate the antibacterial capabilities of Actinomycetes from the rhizosphere of olive tree (Olea europaea) in the Souk Ahras region, northeastern Algeria. Two actinomycete strains, S4 and S6, were collected by selective culture and then characterized morphologically, physiologically, and biochemically. Their antibacterial properties were evaluated against three pathogenic bacteria: Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli, using the well diffusion method. The strains demonstrated significant inhibitory effects on Staphylococcus aureus and Pseudomonas aeruginosa, and the results indicate that the olive rhizosphere constitutes a rich source of bioactive Actinomycetes, potentially useful for antibiotic development and biological control. This study provides a better understanding of the microbial diversity of the rhizosphere. --------------------------------------------------------------------------------------------------------------------------------------------------- يهدف هذا العمل إلى دراسة الفاعلية المضادة للبكتيريا للبكتيريا الشعاعية المعزولة من منطقة جذور أشجار الزيتون (Olea europaea) في منطقة سوق أهراس، شمال شرق الجزائر. تم جمع سلالتين من الفطريات الشعاعية S4 و S6 عن طريق العزل ومن تم تشخيصها مورفولوجيا وفيزيولوجيا وبيوكيميائيا. تم تقييم خصائصها المضادة للبكتيريا ضد ثلاث بكتيريا مسببة للأمراض: المكورات العنقودية الذهبية، الزائفة الزنجارية والإشريكية القولونية، بواسطة طريقة الانتشار البئري. وأظهرت السلالات تأثيرات مثبطة كبيرة على المكورات العنقودية الذهبية والزائفة الزنجارية، وتشير النتائج إلى أن منطقة جذور الزيتون تشكل مصدرا غنيا بالفطريات الشعاعية النشطة بيولوجيا، والتي قد تكون مفيدة لتطوير المضادات الحيوية. توفر هذه الدراسة فهما أفضل للتنوع الميكروبي في منطقة الجذور. --------------------------------------------------------------------------------------------------------------------------------------------------- Cette étude vise à étudier les capacités antibactériennes des Actinomycètes issus de la rhizosphère d'oliviers (Olea europaea) dans la région de Souk Ahras, au nord-est de l'Algérie. Deux souches d'Actinomycètes S4 et S6 ont été collectées par culture sélective, puis caractérisées morphologiquement, physiologiquement et biochimiquement. Leurs propriétés antibactériennes ont été évaluées vis-à-vis trois bactéries pathogènes: Staphylococcus aureus, Pseudomonas aeruginosa et Escherichia coli, par la méthode de diffusion sur puits. Les souches ont démontré des effets inhibiteurs significatifs sur Staphylococcus aureus et Pseudomonas aeruginosa, et les résultats indiquent que la rhizosphère d'olivier constitue une riche source d'Actinomycètes bioactifs, potentiellement utiles pour le développement d'antibiotiques et la lutte biologique. Cette étude permet de mieux comprendre la diversité microbienne des rhizosphères.
Keywords: Actinomycetes; rhizosphere; olive tree; antibacterial activity; pathogenic bacteria. الفطريات الشعاعية، منطقة الجذور، شجرة الزيتون، النشاط المضاد للبكتيريا، البكتيريا المسببة للأمراض. Actinomycètes; rhizosphère; olivier; activité antibactérienne; bactéries pathogènes.